2021
DOI: 10.1097/jbr.0000000000000091
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the quantity and quality of platelet-rich plasma and platelet-derived growth factor-BB: an observational study

Abstract: Objective: Platelet-rich plasma (PRP) releases growth factors upon activation, which in turn accelerates healing and regeneration of the target tissue. However, PRP composition may vary according to the patient's demographics, and wider applications of PRP warrant product standardization. The current study aimed to examine variables influencing the platelet-derived growth factor BB (PDGF-BB) concentration in PRP. Methods: This observational study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Verma et al found no significant associations between age, gender and platelet count and growth factors concentration (23). Their results were similar to Cho (24), Dragoo (25) and Arun (26).…”
Section: Discussionsupporting
confidence: 55%
“…Verma et al found no significant associations between age, gender and platelet count and growth factors concentration (23). Their results were similar to Cho (24), Dragoo (25) and Arun (26).…”
Section: Discussionsupporting
confidence: 55%
“…It was reported that keeping the platelet distribution width within the normal ranges indicates good viability of the platelets. 39 Analysis showed that the platelet distribution width was within the physiological reference ranges, and the PRP procedure in this study did not cause preactivation of the platelets. Verma et al 39 emphasized that the platelet distribution width analysis may serve as a measure of quality for PRP activation.…”
Section: Discussionsupporting
confidence: 51%
“… 37 , 38 Higher platelet concentrations may not directly indicate a high-quality PRP alone. 39 On the contrary, over-concentrating platelets with increased growth factor concentrations do not enhance the regenerative properties of PRP and may delay the natural healing process by causing increased scar tissue formation. 40 , 41 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations